1969
DOI: 10.1128/jvi.3.6.627-628.1969
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Genetic Mapping of the SPO2 Prophage on the Chromosome of Bacillus subtilis 168

Abstract: It has been found by density transfer and genetic mapping experiments that prophage SPO2 is linked to the antibiotic resistance marker ery-l in Bacillus subtilis 168. A site for the attachment of the prophage bacteriophage SPO2 (4) has been found on the chromosome of Bacillus subtilis 168. From transduction studies with phage PBS1 (7), the site was found to be closely linked to the erythromycin locus, ery-J (3). An approximate physical localization of the SPO2 prophage on the genetic map was first obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…on September 4, 2020 by guest http://mmbr.asm.org/ Downloaded from ences, however. They integrate at different positions on the host genome (136,263), and have dissimilar immunities as evidenced by the fact that double lysogens are easily prepared (242). Moreover, mutants of SP02 and 4105 do not complement one another in appropriate mixed infections, and they do not undergo heterologous genetic recombination (267).…”
Section: Bacteriol Revmentioning
confidence: 99%
See 1 more Smart Citation
“…on September 4, 2020 by guest http://mmbr.asm.org/ Downloaded from ences, however. They integrate at different positions on the host genome (136,263), and have dissimilar immunities as evidenced by the fact that double lysogens are easily prepared (242). Moreover, mutants of SP02 and 4105 do not complement one another in appropriate mixed infections, and they do not undergo heterologous genetic recombination (267).…”
Section: Bacteriol Revmentioning
confidence: 99%
“…The location of the SP02 and 4)105 prophages on the B. subtilis genome and the order of genes in the integrated state have been investigated by means of transformation and PBS1 transduction. Inselburg and co-workers (136) found that the SP02 prophage co-transduced 60 to 65% with the erythromycin marker (ery-1) and 20% with a cysteine locus (cysAl4); fourfactor crosses demonstrated the gene order to be sul-cysAl4-ery-1-SP02, where sul is sulfanilimide resistance. More precise mapping has shown that the SP02 attachment site is located between spc-2 and lin-2 which are, respectively, sites conferring resistance to the antibiotics spectinomycin and lincomycin (292).…”
Section: Sp82gmentioning
confidence: 99%
“…Two temperate bacteriophages have been identified for B. subtilis: SPO2 (isolated by Okubo) and k105 (isolated by Reilly). These bacteriophages (i) integrate linearly into the bacillus chromosome at two different attachment sites (17,25,34), (ii) have different receptors, and (iii) are heteroimmune (6). Previously, we reported that the frequency of DNA-mediated transformation was reduced in cells lysogenic for 0105, whereas no reduction occurred in the frequency of transfection with DNA isolated from bacteriophages 029 and SPOl (31).…”
mentioning
confidence: 99%
“…Two of the bacteriophages, 0105 and SPO2, have DNA with the same molecular weight and are morphologically similar (2,3,16). Bacteriophages SPO2 and k105 are certainly different in that they are heteroimmune (2), integrate at different locations in the host chromosome (9,17), and only share approximately 14% base sequence homology as determined by electron microscopy of heteroduplex DNA molecules (4). In addition, Chow and Davidson (5) demonstrated that the SPO2 prophage is a circular permutation of the mature phage, whereas 0105 prophage and mature phage are colinear.…”
mentioning
confidence: 99%